Comparison of ultrasound- vs. landmark-guided injections for musculoskeletal pain: an umbrella review - Peng-Chieh Shen; Ting-Yu Lin; Wei-Ting Wu; Levent Özçakar; Ke-Vin Chang (Medical Journals Sweden, 2024)
Objective: This umbrella review synthesizes systematic reviews and meta-analyses to reach a conclusion concerning the overall effectiveness of ultrasound-guided vs landmark-guided injections for treating musculoskeletal pain. Design: Umbrella review. Methods: PubMed, EMBASE, MEDLINE, and Web of Science were searched for relevant systematic reviews and meta-analyses from inception to March 2024. Critical appraisal, data extraction, and synthesis were performed in accordance with the criteria for conducting an umbrella review. Results: Seventeen articles, comprising 4 systematic reviews and 13 meta-analyses, were included. Using the AMSTAR2 instrument for quality assessment, 3 articles were rated as high quality, 1 as moderate, 7 as low, and 6 as critically low. Generally, ultrasound-guided injections were found to be more accurate than landmark-guided injections, particularly in the shoulder joint, though the results for pain relief and functional outcomes varied. Ultrasound guidance was notably effective for injections into the bicipital groove, wrist, hip, and knee - yielding greater accuracy and improved pain management. Both ultrasound-guided and landmark-guided techniques showed low incidence of adverse effects. Conclusion: This umbrella review offers an in-depth analysis of the comparative effectiveness of ultrasound-guided and landmark-guided injections across a range of musculoskeletal sites/conditions. The findings suggest that ultrasound-guided is a reliable method.